Relationship between Daytime Sleepiness and Health Utility in Patients after Cardiac Surgery: A Preliminary Study - Izawa, Kazuhiro P. (Int J Environ Res Public Health, 2018)
Background Daytime sleepiness can be assessed by the Epworth Sleepiness Scale (ESS), which is widely used in the field of sleep medicine as a subjective measure of a patient’s sleepiness. Also, health utility assessed by the mean Short-Form Six-Dimension (SF-6D) score, one of several preference-based utility measures, is an important measure in health care. We aimed to examine age-related differences in daytime sleepiness and health utility and their relationship in patients 5 months after cardiac surgery. Methods; This cross-sectional study assessed 51 consecutive cardiac surgery patients who were divided into a middle-aged (<65 years, n = 29) and older-age group (≥65 years, n = 22). The mean ESS and SF-6D utility scores were measured at 5 months after cardiac surgery and compared. In addition, the relationship between ESS and SF-6D utility scores were assessed. Results; There were no significant differences between the middle-aged and older-aged groups in either the mean ESS (5.14 ± 2.96 vs. 4.05 ± 3.23, p = 0.22) or SF-6D utility (0.72 ± 0.14 vs. 0.71 ± 0.10, p = 0.76) scores. However, there was a negative correlation between both values in all of the patients after cardiac surgery (r = −0.41, p = 0.003). Conclusions; Although there were no age-related differences in the ESS and SF-6D utility values between the two groups, there was a negative correlation between these values in all patients at 5 months after cardiac surgery. This suggested that sleepiness is associated with decreased utility scores in patients at 5 months after cardiac surgery.